2018
DOI: 10.1080/13102818.2018.1447397
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships and diversity among wild Salvia accessions revealed by ISSR and SCoT markers

Abstract: In this study, inter-simple sequence repeats (ISSR) and start codon targeted (SCoT) markers were used for genetic diversity and relationship analysis of nine Salvia species. Twenty-one and twenty selected ISSR and SCoT primers amplified 350 and 329 loci, respectively, of which all were polymorphic. The obtained average polymorphism information content (ISSR, 0.38; SCoT, 0.40), average band informativeness (ISSR, 16.67; SCoT, 16.45) and resolving power (ISSR, 9.75; SCoT, 12.52) revealed high genetic diversity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 27 publications
7
29
0
Order By: Relevance
“…In contrast, the average Rp value of the CBDP markers was more than that of the SCoT markers, which indicated the high ability of the CBDP markers to reflect the genetic diversity in T. urartu. These results are in agreement with Heikrujam et al [36], Tiwari et al [9], Etminan et al [16,17,37] and Qaderi et al [19], who reported that SCoT and CBDP markers were more useful for dissecting genetic diversity and structure than other molecular marker techniques.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, the average Rp value of the CBDP markers was more than that of the SCoT markers, which indicated the high ability of the CBDP markers to reflect the genetic diversity in T. urartu. These results are in agreement with Heikrujam et al [36], Tiwari et al [9], Etminan et al [16,17,37] and Qaderi et al [19], who reported that SCoT and CBDP markers were more useful for dissecting genetic diversity and structure than other molecular marker techniques.…”
Section: Resultssupporting
confidence: 90%
“…The CAAT box region has a specific pattern of nucleotides with a consensus sequence and is located upstream of the start codon of eukaryotic genes [14]. Due to several advantages such as repeatability, low cost and high polymorphism, these techniques have been successfully applied in genetic diversity studies of many plant species [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Both of these techniques indicated low genetic diversity at population level and high genetic diversity at species level, and showed a similar clustering of H. serrata populations. The present study showed that using independent data from two different techniques can present a more efficient and accurate way to survey the genetic variability of a given species [21].…”
Section: Usability Of the Used Techniquesmentioning
confidence: 83%
“…This technique was proposed to be used in conjunction with other DNA fingerprinting techniques for applications such as genetic analysis, and quantitative trait loci mapping, especially in laboratories with a preference for agarose gel electrophoresis [10]. Thus, the ISSR and SCoT markers have been successfully used for quantification of genetic diversity in different plants [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The Shannon diversity index values calculated from both TRAPs and CoRAPs were consistent with the species genetic variability level. Comparable PIC values have been reported with dominant markers like RAPD and AFLP in African plantain (Musa paradisiaca) [42], ISSRs and RAPDs in Salvia species [40], AFLP in wheat (Triticum aestivum) [43] and SCoT markers [44][45][46][47][48]. TRAP and CoRAP are relatively high-throughput PCRbased marker systems; they appear to be very efficient relative to other systems.…”
Section: Corap Analysismentioning
confidence: 86%